2012
DOI: 10.1521/jscp.2012.31.9.972
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Mechanisms in the Relationships between Dependency/Self-Criticism and Depressive Symptoms in Taiwanese Undergraduates: A Prospective Study

Abstract: The present study investigated the relationships among depressogenic personality styles (dependency and self-criticism), interpersonal behaviors, and depressive symptoms. The sample consisted of 84 college students in Taiwan (89% female; 11% male), ranging in age from 18 to 24 (M = 19.39; SD = 1.31). At both baseline and 6-month follow-up, participants completed the Depressive Experiences Questionnaire

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
4
10
0
Order By: Relevance
“…in an attempt to mitigate potential losses in rank, self-critical individuals are likely to submit to dominant others rather than engage in competition which, if lost, could result in an even greater loss of social status. this finding is consistent with low mean levels of agency in self-critics (Liu et al, 2012;Zuroff et al, 1999). However, the dominant or submissive behavior of self-critics may also fluctuate in an attempt to mitigate potential losses in status relative to others.…”
supporting
confidence: 75%
See 3 more Smart Citations
“…in an attempt to mitigate potential losses in rank, self-critical individuals are likely to submit to dominant others rather than engage in competition which, if lost, could result in an even greater loss of social status. this finding is consistent with low mean levels of agency in self-critics (Liu et al, 2012;Zuroff et al, 1999). However, the dominant or submissive behavior of self-critics may also fluctuate in an attempt to mitigate potential losses in status relative to others.…”
supporting
confidence: 75%
“…Given the association of both the personality factors measured here and behavioral variability with negative interpersonal outcomes (e.g., côté et al, 2012; Kopala-sibley, Russell et al, 2007), future research would benefit from examining whether behavior variability accounts for the relationship between self-criticism and connectedness and interpersonal outcomes. indeed, one recent study found that behavioral variability partially accounts for the associations between self-criticism, dependency, and depressive symptoms (Liu et al, 2012). concLusion this study found that higher levels of self-criticism were associated with more flux in dominance, submissiveness, and agreeableness, as well as more spin, and connectedness was associated with lower levels of spin.…”
Section: Connectedness and Behavioral Variabilitymentioning
confidence: 47%
See 2 more Smart Citations
“…The shortest time-frame was just 7 weeks (Sturman et al, 2015) and the longest time-frame was 10 years (Brewin & Firth-Cozens, 1997). Looking at the retention of participants over time, only five studies retained at least 80% of participants by T2 (Gautreau et al, 2015;Liu et al, 2012;McGrath et al, 2012, Sherry et al, 2013& Sherry et al, 2014 and only one study retained at least 80% of participants by T3 and T4 (McGrath et al 2012). Four studies did not report their retention/attrition rates (Priel & Shahar, 2000;Shahar, 2006;Spasojevic & Alloy, 2001;Yao et al, 2009).…”
Section: Longitudinal Designmentioning
confidence: 99%